2015
DOI: 10.1242/bio.013011
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific comparison of sleep acquisition systems in Drosophila

Abstract: Sleep is conserved across phyla and can be measured through electrophysiological or behavioral characteristics. The fruit fly, Drosophila melanogaster, provides an excellent model for investigating the genetic and neural mechanisms that regulate sleep. Multiple systems exist for measuring fly activity, including video analysis and single-beam (SB) or multi-beam (MB) infrared (IR)-based monitoring. In this study, we compare multiple sleep parameters of individual flies using a custom-built video-based acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 38 publications
4
67
0
Order By: Relevance
“…A number of systems have been developed for high-resolution video tracking that may provide a more accurate measure of sleep compared to infrared-based monitoring systems [1417]. Tracking analysis revealed that w 1118 control, but not trsn null flies, suppress sleep during starvation, confirming that the results obtained using infrared tracking are not an artifact of the sleep acquisition system (Figure S1F).…”
Section: Resultsmentioning
confidence: 73%
“…A number of systems have been developed for high-resolution video tracking that may provide a more accurate measure of sleep compared to infrared-based monitoring systems [1417]. Tracking analysis revealed that w 1118 control, but not trsn null flies, suppress sleep during starvation, confirming that the results obtained using infrared tracking are not an artifact of the sleep acquisition system (Figure S1F).…”
Section: Resultsmentioning
confidence: 73%
“…3B) and the strong increase in micro-movements (Fig. 3C) are likely to represent an increase in food intake and egg-laying activity and may explain why such a strong decline in sleep amount was never identified using different tools (27,43,44). Interestingly, four-dimensional behavioural fingerprinting showed that the short sleep phenotype observed upon mating is qualitatively different from the one observed as natural variation in the CantonS population ( …”
Section: Qualitatively Different Types Of Short Sleeping Femalesmentioning
confidence: 94%
“…This system, however, provides only limited spatial resolution which -unsurprisingly -results in an overestimation of sleep amounts (27). A growing number of laboratories are therefore transitioning to more accurate systems based on computer assisted video-tracking (27)(28)(29)(30)(31).…”
Section: Virtually Sleepless Flies Are Found In a Non-mutant Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…This concerns mice [12]- [14], Caenorhabditis elegans [15]- [17], as well as Drosophila flies [18]- [22]. However, to the best of our knowledge there is no system available for monitoring the behaviour of Drosophila at the larval states in culture vials for a long time period.…”
Section: Introductionmentioning
confidence: 99%